A Comparative Study between Delineation of Radiotherapy Target Volumes with and Without Peritumoral Edema for Patients with Postoperative Glioblastoma Multiforme - Hoq, Tania; Ferdous, Jannatul; Ali, Md Yousuf (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Glioblastoma Multiforme (GBM) is an aggressive primary brain tumor with a poor prognosis. Radiotherapy is a critical component of GBM treatment, but the optimal delineation of the clinical target volume (CTV), particularly regarding the inclusion of peritumoral edema, remains debated. This study aimed to compare the clinical outcomes and toxicities in GBM patients treated with radiotherapy that includes or excludes peritumoral edema in the CTV. Methods: This quasi-experimental, non-randomized prospective study was conducted over 12 months at the Department of Radiation Oncology, National Institute of Cancer Research and Hospital, Dhaka. Sixty postoperative GBM patients were enrolled and divided into two arms: Arm A (CTV including peritumoral edema) and Arm B (CTV excluding peritumoral edema). Clinical outcomes, including treatment response and toxicities, were assessed at 6 weeks and 6 months post-treatment. Results: The baseline characteristics were well-matched between the two arms. At 6 weeks, the complete response (CR) rates were comparable between the two arms, with no significant difference. After 6 months, CR rates remained similar between Arm A (60.0%) and Arm B (53.3%), with no significant difference. However, Arm A exhibited significantly higher rates of toxicities, including nausea, vomiting, and headaches. Arm B showed lower toxicity levels, with fewer cases of severe vomiting and headaches. Conclusion: The exclusion of peritumoral edema from the CTV results in similar tumor control compared to its inclusion, but with significantly lower toxicity levels. These findings suggest that excluding peritumoral edema from the CTV may be a preferable strategy for postoperative GBM management, offering comparable efficacy with reduced side effects. J Bangladesh Coll Phys Surg 2025; 43: 197-204